2014
DOI: 10.2460/ajvr.75.4.361
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution manometric evaluation of the effects of cisapride and metoclopramide hydrochloride administered orally on lower esophageal sphincter pressure in awake dogs

Abstract: Results suggested that orally administered cisapride may be of benefit in canine patients for which an increase in LES pressure is desirable, whereas orally administered metoclopramide did not affect LES resting pressures in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 18 publications
1
31
3
Order By: Relevance
“…However, before the adoption of the HRM in people, contrast swallow studies were used to diagnose LES achalasia and, although only moderately sensitive, were considered highly specific for this condition . Only a few manometric studies in dogs with ME have been performed, and these did not identify LES achalasia to the extent documented in our study . The response to treatment in our patient population makes misdiagnosis unlikely, and this discrepancy between our study and previous studies may reflect limitations in available diagnostic tests at the time those studies were performed.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, before the adoption of the HRM in people, contrast swallow studies were used to diagnose LES achalasia and, although only moderately sensitive, were considered highly specific for this condition . Only a few manometric studies in dogs with ME have been performed, and these did not identify LES achalasia to the extent documented in our study . The response to treatment in our patient population makes misdiagnosis unlikely, and this discrepancy between our study and previous studies may reflect limitations in available diagnostic tests at the time those studies were performed.…”
Section: Discussioncontrasting
confidence: 55%
“…High‐resolution manometry is considered the gold standard for diagnosis of LES achalasia in people. Unfortunately, this modality is not routinely performed in veterinary medicine because of limited availability, high cost, need for operator expertise, and patient compliance . However, before the adoption of the HRM in people, contrast swallow studies were used to diagnose LES achalasia and, although only moderately sensitive, were considered highly specific for this condition .…”
Section: Discussionmentioning
confidence: 78%
“…Management of intestinal leiomyositis in humans is supportive generally and aimed at relieving signs arising from intestinal dysmotility as well as optimizing nutritional support . Prokinetic treatment is a mainstay of treatment, and cisapride has been shown to increase the antroduodenal motility index and improve enteral feeding in people as well as to increase lower esophageal sphincter (LES) pressure and decrease gastroesophageal reflux in dogs . Metoclopramide is a less potent and effective prokinetic agent compared to cisapride in dogs .…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacological approaches, especially with prokinetic drugs such as metoclopramide, domperidone or cisapride, have been proposed, with modest or varying results (Washabau 2003). However, recent studies with high-resolution manometry showed that cisapride significantly increased LOS pressure in healthy dogs, and this could represent a serious concern in dogs with megaoesophagus (Kempf and others 2014, Ullal and others 2016). …”
Section: Introductionmentioning
confidence: 99%